Musykilaat al-Thullaab Fii Ta'allum al-Lughat al-'Arabiyyat wa Muhaawalaat al-Mudarrisiin li Hillihaa li al-fashl al-I'daadi bi Jaami'at Daar al-Salaam Gontor Ponorogo - M. Miftahul Ulum; Naufal Fikri (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Matriculation language program is an intensive language program started on 2016 at University of Darussalam Gontor (UNIDA) to prepare new students who doesn’t fluency in English and Arabic language, especially for English and Arabic tests. It is also crucial for thesis writing, at UNIDA. The objectives of this study are: (1) to find students' problems in learning Arabic programme matriculation in the academic year 2019-2020; and (2) to find out the teacher's efforts in providing solutions in matriculation problems. This research is a qualitative descriptive study. The results found that: (1) problems of learning arabic students caused by the following factors: (a) many students who participated in non-linguistic activities at UNIDA; (b) lack of enthusiasm and encouragement from students; (c) students have not consider the importance of this program; (d) the lack of providing guidance and good advice to students from the teachers; and (e) the students do not want to be regulated in learning arabic. The teachers efforts to solve these problems are: (a) emphasizing the rules of language with a place that is set with a special boarding system; (b) watching arabic films and discussions and giving praise, gifts for students who are active in this program; (c) teachers should be good examples in speaking arabic; (d) meeting after language skills training; and (e) make fun of language activities for example; competitions, games, and quarantine in arabic